1998
DOI: 10.1103/physrevd.58.057503
|View full text |Cite
|
Sign up to set email alerts
|

Scalar glueball mass in Regge phenomenology

Abstract: We show that linear Regge trajectories for mesons and glueballs, and the cubic mass spectrum associated with them, determine a relation between the masses of the ρ meson and the scalar glueball, M (0 ++ ) = 3/ √ 2 M (ρ), which implies M (0 ++ ) = 1620 ± 10 MeV. We also discuss relations between the masses of the scalar and tensor and 3which imply M (2 ++ ) = 2290 ± 15 MeV, M (3 ++ ) = 3240 ± 20 MeV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A general expression for the Pomeron trajectory can be expressed as α P (t) = α P (0) + α P · t, where t is related to the dispersion relation, t = 4(k 2 + m 2 ). The latest values of α P (0) and α P are determined by experiments [48][49][50], α P (0) ∼ 1.08 and α P = 0.2 GeV −2 .…”
Section: Results and Conclusionmentioning
confidence: 99%
“…A general expression for the Pomeron trajectory can be expressed as α P (t) = α P (0) + α P · t, where t is related to the dispersion relation, t = 4(k 2 + m 2 ). The latest values of α P (0) and α P are determined by experiments [48][49][50], α P (0) ∼ 1.08 and α P = 0.2 GeV −2 .…”
Section: Results and Conclusionmentioning
confidence: 99%
“…We emphasize that at this time there is no convincing proof that the pomeron is a glueball. As to the ξ(2230) meson itself, it can either be a tensor glueball or a q q−glue mixture [13][14][15][16][17]. Close Frank [15] has shown that if ξ is a tensor glueball then its total width tot would be of the order of 25 MeV; but no discussion was made on the ξ →pp .…”
Section: L61mentioning
confidence: 99%
“…Eqs. (9) and (13) to (16) allow us to predict the decay width Γ ξ→pp from the measured pp total and elastic cross sections, and vice versa. We have determined the form factor parameters from the experimental pp total and elastic cross sections data [1] [6] at √ s = 53 and 62 GeV.…”
mentioning
confidence: 99%
“…On the other hand in the quark jet neither the hybrid nor the glueball will be leading if the leading quark is only neutralized in color by a soft antiquark. As it is note by Burakovsky [9] it is widely believed that pseudoscalar mesons are the Goldstone bosons of broken SU(3)×SU(3) chiral symmetry of QCD, and that they should be massless in the chirally symmetric phase. Because that it is not clear how the resonance spectrum would be suitable for the description of the pseudoscalar mesons.…”
Section: Discussionmentioning
confidence: 99%